Anatolij Svidzynskyj's 85th birthday (Condensed Matter Physics, 2014)
This year a prominent Ukrainian theoretical physicist and public leader Anatolij Svidzynskyj marks his 85th birthday. Anatolij Svidzynskyj was born on 1 March 1929 in Mohyliv-Podilskyy (Ukraine) to a family of a physics teacher and an economist. Since 1939 and to the end of WWII Svidzynskyj's family lived in Kiev. In 1945 they moved to Lviv, where A. Svidzynskyj graduated from the Faculty of Physics and Mathematics of the Lviv State University. Vasyl Milyanchuk was his first supervisor. Due to his advice A. Svidzynskyj moved to Moscow State University where Mykola Boholiubov worked at the time. Under Bogoliubov's supervision the PhD thesis ``On the method of functional averaging in the theory of Green's function'' was written, which was defended in 1956 at Lviv State University. One of the most important results obtained in the thesis is an exact solution of Bloch-Nordsieck model that describes an infrared asymptotic of the electron Green's function in a realistic theory - quantum electrodynamics. In this way, a non-analytical dependence of this function on a coupling constant was obtained, and the nature of infrared divergences in quantum electrodynamics was clarified.